36.3k views
5 votes
How do I solve this literal equation?
15 points

How do I solve this literal equation? 15 points-example-1
User Franchb
by
5.2k points

1 Answer

5 votes

Answer:


\pi = (A)/(2r^2 + 2rh)

Explanation:

First, we need to isolate
\pi by taking it common from both terms on the right:


A=2\pi r^2 + 2\pi rh\\A=\pi (2r^2 + 2rh)

Now, since we want
\pi in terms of the other variables, we can divide the left hand side (A) by whatever is multiplied with
\pi on the right hand side. Then we will have an expression for
\pi. Shown below:


A=\pi (2r^2 + 2rh)\\\pi = (A)/(2r^2 + 2rh)

This is the xpression for
\pi

User Saman Jahangiri
by
4.7k points